Suicidal and violent ideation in acute psychiatric inpatients: prevalence, co‐occurrence, and associated characteristics. Issue 3 (26th December 2020) - Furnes, Desiré; Gjestad, Rolf; Rypdal, Knut; Mehlum, Lars; Hart, Stephen; Oedegaard, Ketil J.; Mellesdal, Liv
Abstract: Objective: We studied the point prevalence of suicidal and violent ideation, as well as their co‐occurrence and associated characteristics in inpatients with mental health disorders. Methods: Data on suicidal and violent ideation, and sociodemographic and clinical information, were gathered from 1, 737 patients when admitted to the acute psychiatric ward. Results: The point prevalence was 51.9% for suicidal ideation and 19.8% for violent ideation. The point prevalence of co‐occurring suicidal and violent ideation was 12.3%, which was significantly greater than expected by chance. Logistic regression analyses indicated that both suicidal and violent ideation were associated with young age and the absence of diagnoses of psychotic disorders; in addition, suicidal ideation was associated with female gender, violent ideation, and diagnoses of mood‐ neurotic and personality disorders, whereas violent ideation was associated with male gender, suicidal ideation, and diagnoses of mood and neurotic disorders. Conclusions: Overall, the findings highlight the need for further research on suicidal and violent ideation in people with mental health problems including, but not limited to, their association with adverse behavioral outcomes, as well as the need to routinely assess both suicidal and violent ideation in clinical practice.